2015
DOI: 10.1021/acs.chemmater.5b00286
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Nucleation and Growth of InP Quantum Dots via Magic-Sized Cluster Intermediates

Abstract: We report on the role of magic-sized clusters (MSCs) as key intermediates in the synthesis of indium phosphide quantum dots (InP QDs) from molecular precursors. Heterogeneous growth from the MSCs directly to InP QDs was observed without intermediate sized particles. These observations suggest that previous efforts to control nucleation and growth by tuning precursor reactivity have been undermined by formation of these kinetically persistent MSCs prior to QD formation. The thermal stability of InP MSCs is infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
507
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(534 citation statements)
references
References 71 publications
(144 reference statements)
26
507
1
Order By: Relevance
“…for crystalline InP 66 , but it is above the typical temperature for InP quantum dot synthesis (450 K) 14,[16][17][18] . Since our simulation only includes indium and phosphorus atoms, rearrangements of the InP(111) model in the AIMD trajectory are completely defined by average instantaneous In-P, In-In, and P-P distances ( Figure 2).…”
Section: A Aimd Sampling For Cluster Generationmentioning
confidence: 94%
See 2 more Smart Citations
“…for crystalline InP 66 , but it is above the typical temperature for InP quantum dot synthesis (450 K) 14,[16][17][18] . Since our simulation only includes indium and phosphorus atoms, rearrangements of the InP(111) model in the AIMD trajectory are completely defined by average instantaneous In-P, In-In, and P-P distances ( Figure 2).…”
Section: A Aimd Sampling For Cluster Generationmentioning
confidence: 94%
“…These larger P-P distances do not necessarily mean that phosphorus atoms aggregate on the surface. In and P atoms have comparable probabilities in the distance to the cluster center of mass (see Supporting Information Figure In order to identify whether features of RDFs are size-dependent, we group clusters as "small" (3-7 pairs), "intermediate" (8)(9)(10)(11)(12)(13)(14), and "large" (15)(16)(17)(18)(19)(20)(21)(22), based in part on energetic trends ( Figure 5). A comparison of RDFs for these three groups (see Supporting Information Figure S8) reveals that small clusters have a shorter distance for the first-minimum in the In-P RDF, which is below 3.1 Å.…”
Section: E Comparing Properties Of Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…The InP quantum dots (QDs) were prepared by a procedure from Gary and Cossairt. 58 One sample consisted of the pure as-synthesized InP QDs, while the second sample consisted of Zn-passivated InP QDs, which were post-synthetically modified with zinc oleate as described in the work of Stein et al 59 The third sample measured was InP magic-sized clusters with the initial carboxylate ligand environment replaced with phosphonates, prepared following a procedure from the work of Gary et al 60 …”
Section: Samplesmentioning
confidence: 99%
“…It has been confirmed that when primary fatty amines were used as ligand in InP quantum dots synthesis, heterogeneous growth of quantum dots from intermediate magic-sized clusters is switched to homogeneous growth from molecular precursors, resulting in narrower size distribution 28 .…”
mentioning
confidence: 92%